THE GROWTH PERFORMANCE OF TILAPIA (Oreochromis niloticus) INFECTED WITH Aeromonas hydrophila BACTERIA WITH ADDITION NUTRIENTS ON FEED - N.P.P., WIJAYANTI; FEBRIANI, D.A.A.; SUDARYATMA, P.E. (Majalah Ilmiah Peternakan; Vol 26 No 1 (2023): Vol. 26 No. 1 (2023)DO - 10.24843/MIP.2023.V26.i01.p02, 2023)
Tilapia (Oreochromis niloticus) is one of the most economically important freshwater fish commodities. But in tilapia fish cultivation activities the emergence of disease becomes one of the problems that affect the quality and quantity of cultivation production. One disease that often appears is the bacterial infection Aeromonas hydrophyla. The problem is expected to be resolved by giving vitamin C in fish feed. The study aimed to look at the growth per- formance of tilapia infected with A. hydrophyla bacteria judging by measurements of length, weight gain, Survival Rate, Feed Conversion Ratio, and water quality parameters such as temperature, pH, and DO (Dissolved Oxygen). The study consisted of 2 controls namely positive control and negative control, as well as 3 treatments with diffe- rent doses of vitamin C. As a positive control (treatment A) is tilapia fish given commercial feed and infected with bacteria with a density of 106 CFU/ml; negative control (treatment B) is fish that are only given commercial feed; treatment C is a fish that is given commercial feed with the addition of vitamin C 150 mg/kg and infected with bac- teria 106 CFU/ml; D treatment is a fish that is given commercial feed with the addition of vitamin C 300 mg/kg and infected with bacteria 106 CFU/ml; and treatment E is a fish that is given commercial feed with the addition of vita- min C 450 mg/kg and infected with bacteria 106 CFU/ml. The results of the study on the weight and length growth parameters infected with A. hydrophyla bacteria experienced shrinkage due to stress and decreased appetite. The survival of tilapia fish given additional vitamin C in feed as much as 150 mg/kg gives the best results.